The Youth in Iceland Model and Icelandic Adolescent Mental Health ... - DeVito, Katerina Maria (Columbia University, 2019)
Over the last 20 years, Iceland has made major progress in reducing substance use among its youth. Many credit this impressive reduction to implementation of the Youth in Iceland (YiI) Model. YiI programming aims to prevent substance use by increasing youth social support through strengthening family relationships, peer relationships, community connection, and community engagement. It involves a wide variety of relevant stakeholders, including policymakers, teachers, parents, and youth workers. Specific programming ranges from recreational sports teams to parental neighborhood watches. While studies have indicated that YiI programming has greatly reduced substance use among youth, new data have suggested that mental health problems are rising among Icelandic adolescents. Despite an increase in the prevalence of mental health problems, no studies have explored the impact of YiI programming on Icelandic youth mental health. This mixed-methods project consisted of three studies that evaluated the effect of YiI ...